Pemanfaatan Ekstrak Rimpang Kunyit (Curcuma domestika v.) Sebagai Zat Warna Pada Sediaan Pewarna Rambut - Meyana Marbun; Arsiaty Sumule; Yulia Delfahedah; Muharti Sanjaya; Dilla Sastia Mara (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2020)
Hair coloring preparations are cosmetic preparations used in hair cosmetology to color hair, either to restore the original hair color or another color. Turmeric rhizome contains alkaloids, flavanoid tannins and essential oils. The purpose of this study was to determine the chemical compounds contained in turmeric rhizome, to make turmeric rhizome change the color of gray hair. Hair dye preparation is made with a formula consisting of a concentration of turmeric extract rhizome, namely 20%. This research method is experimental by using maceration method. Physical evaluation carried out included homogeneity test, irritation test, color stability test against sun exposure, color stability test against washing. The results of this study indicate that turmeric rhizome extract can affect the color of the gray hair obtained. The stability test against washing can last for 5 times washing, the stability test against sunlight shows that the hair turns darker than before.